1)
[tex] \frac{18}{30} - x = \frac{4}{30} + \frac{6}{30} \\ \frac{18}{30} - x = \frac{10}{30} \\ x = \frac{18}{30} - \frac{10}{30} \\ x = \frac{8}{30} \\ x = \frac{4}{15} [/tex]
2)
[tex]( \frac{13}{67} + \frac{6}{67} ) - x = \frac{9}{67} \\ \frac{19}{67} - x = \frac{9}{67} \\ x = \frac{19}{67} - \frac{9}{67} \\ x = \frac{10}{67} [/tex]
3)
[tex] \frac{10}{15} + ( \frac{5}{15} - x) = \frac{14}{15} \\ \frac{5}{15} - x = \frac{14}{15} - \frac{10}{15} \\ \frac{5}{15} - x = \frac{4}{15} \\ x = \frac{5}{15} - \frac{4}{15} \\ x = \frac{1}{15} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1)
[tex] \frac{18}{30} - x = \frac{4}{30} + \frac{6}{30} \\ \frac{18}{30} - x = \frac{10}{30} \\ x = \frac{18}{30} - \frac{10}{30} \\ x = \frac{8}{30} \\ x = \frac{4}{15} [/tex]
2)
[tex]( \frac{13}{67} + \frac{6}{67} ) - x = \frac{9}{67} \\ \frac{19}{67} - x = \frac{9}{67} \\ x = \frac{19}{67} - \frac{9}{67} \\ x = \frac{10}{67} [/tex]
3)
[tex] \frac{10}{15} + ( \frac{5}{15} - x) = \frac{14}{15} \\ \frac{5}{15} - x = \frac{14}{15} - \frac{10}{15} \\ \frac{5}{15} - x = \frac{4}{15} \\ x = \frac{5}{15} - \frac{4}{15} \\ x = \frac{1}{15} [/tex]